The role of women in extension work - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
From 24 to 29 May, 1987, at Sparsholt, England, CTA, in conjunction with the Royal Agricultural Society of England and the British Council, organized a seminar to discuss the contribution of women to rural extension